Diagnosis of "Poorly Formed Glands" Gleason Pattern 4 Prostatic Adenocarcinoma on Needle Biopsy. (October 2015) - Zhou, Ming; Li, Jianbo; Cheng, Liang; Egevad, Lars; Deng, Fang-Ming; Kunju, Lakshmi Priya; Magi-Galluzzi, Cristina; Melamed, Jonathan; Mehra, Rohit; Mendrinos, Savvas; Osunkoya, Adeboye O.; Paner, Gladell; et al.
<x xml:space="preserve">Abstract</x> Accurate recognition of Gleason pattern (GP) 4 prostate carcinoma (PCa) on needle biopsy is critical for patient management and prognostication. "Poorly formed glands" are the most common GP4 subpattern. We studied the diagnostic reproducibility and the quantitative threshold of grading GP4 "poorly formed glands" and the criteria to distinguish them from tangentially sectioned GP3 glands. Seventeen urologic pathologists were first queried for the definition of "poorly formed glands" using cases representing a spectrum of PCa glandular differentiation. Cancer glands with no or rare lumens, elongated compressed glands, and elongated nests were considered "poorly formed glands" by consensus. Participants then graded a second set of 23 PCa cases that potentially contained "poorly formed glands" with a fair interobserver agreement (κ=0.34). The consensus diagnoses, defined as agreement by >70% participants, were then correlated with the quantitative (⩽5, 6 to 10, >10) and topographic features of poorly formed glands (clustered, immediately adjacent to, and intermixed with other well-formed PCa glands) in each case. Poorly formed glands immediately adjacent to other well-formed glands regardless of their number and small foci of ⩽5 poorly formed glands regardless of their location were not graded as GP4. In contrast, large foci of >10 poorly formed glands that were not immediately adjacent to well-formed glands were graded as GP4. Grading "poorly formed glands" is challenging. Some morphologic features are, however, reproducible for and against a GP4 diagnosis. This study represents an important step in standardization of grading of "poorly formed glands" based on quantitative and topographic morphologic features.